A COMPARATIVE STUDY OF THE EFFECT OF DIFFERENT TECHNIQUES OF COOPERATIVE LEARNING AND SELF-CONFIDENCE UPON STUDENTS’ SPEAKING COMPETENCY - Joni, D. A. A. W.; Nitiasih, P.K.; Artini, L.P. (International Journal of Language and Literature, 2017)
This study focused on: 1) investigating the significant difference in speaking competency between the students taught by using Jigsaw II and those taught by using STAD; 2) investigating the interactional effect between teaching techniques and self-confidence upon students’ speaking competency; 3) investigating the significant difference in speaking competency between the students with high self-confidence taught by Jigsaw II and those taught by STAD; and 4) investigating the significant difference in speaking competency between the students with low self-confidence taught by Jigsaw II and those taught by STAD. The findings show that, firstly, the students treated by Jigsaw II achieve better speaking competency than those treated by STAD; secondly, there is an interactional effect between teaching techniques and self-confidence on the students’ speaking competency; thirdly, the students with high-self-confidence gain higher speaking competency when being treated by Jigsaw II than by STAD; and fourthly, the students with low self-confidence attain the same speaking competency achievement when being treated by Jigsaw II and STAD.